A composite catalytic reforming electrode with perovskite catalyst and Ni foam for high efficient CH4-fueled solid oxide fuel cell - Wei Luo; Yong Yang; Qinzhong Chen; Mingjun Li; Peng Qiu; Manqing Yang; Kang Li; Yangbo Jia; Renhong Li; Tong Wei (Chemical Engineering Journal, 2026)

Visuotactile multimodal fusion with flexible piezo-triboelectric sensors for high-fidelity piano keystroke dynamics decoding - Liang Shen; Man Li; Tingxuan Chen; Qinhua Hu; Bowen Zhang; Enjie Wang; Ji Luo; Mingjun Zhang; Wenjie Wu; Wei Tao (Chemical Engineering Journal, 2026)

Stability assessment of CO2 hydrate in marine sediments using millennial-scale methane hydrate as a natural benchmark - Lei Zhang; Wei Song; Yuanyuan Cui; Pengfei Wang; Mingjun Yang; Bingbing Chen; Yongchen Song (Journal of Environmental Chemical Engineering, 2026)

Seepage-path-dependent CO2 hydrate formation and storage capacity enhancement in NGH reservoirs - Ziming Yang; Lei Zhang; Yufeng Jiang; Bingbing Chen; Mingjun Yang (Fuel, 2026)

Activation of periodate driven by the synergistic interaction between inherent soil Fe and organic matter for adiazine degradation: Mechanisms, soil-type effects, and soil property changes - Yue Zhang; Caixia Yan; Yabing Chen; Yuyan Liu; Mingjun Ding; Peng Wang; Haofeng Liu; Minghua Nie (Journal of Hazardous Materials, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Modeling Hydrate Formation Kinetics and Permeability Evolution: A New Approach Integrating Different Gas-Liquid Contact Modes - Yongqiang Xia; Bingbing Chen; Lanlan Jiang; Lei Yang; Mingjun Yang; Tao Yu; Yongchen Song (Gas Science and Engineering, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Electrostatic interaction induced enhancement of conductive hydrogel for motion detection and targeted identification of ascorbic acid in sweat - Jiarui Liu; Xianghe Zheng; Xinhang Yu; Mingjun Jia; Kai Wei; Liangjiu Bai; Wenxiang Wang; Kun Yin; Lixia Yang; Hou Chen (Analytica Chimica Acta, 2026)

Enhanced selective leaching of Ni and Co via pre-oxidizing and high-pressure acid leaching of Ni-Co-Fe powder - Jing Chen; Yuqi Zhong; Jun Luo; Xin Zhang; Mingjun Rao; Zhiwei Peng; Guanghui Li; Tao Jiang (Hydrometallurgy, 2026)

Condensate gas adsorption and desorption behavior on continental shale matrix under retrograde condensation effect - Mingjun Chen; Maoling Yan; Yili Kang; Hua Liu; Xiaohu Hu; Gang Xiong; Zhehan Lai; Jiajia Bai (Chemical Engineering Journal, 2026)

Multilayer-like peptide-lipid nanoparticles enable effective p53 mRNA delivery for tumor suppression in non-small cell lung cancer - Zhe Wang; Weisi Yuan; Meiping Song; Mingjun Zhang; Chunpeng Yang; Weibang Xia; Jiao Chen; Yuhong Zhen; Yu Liu; Hongxu Liu; Yunming Wang; Yinan Zhao; et al. (Chemical Engineering Journal, 2026)

CTAB regulated front-end synthesis of schwertmannite for rapid high-capacity as(III) removal with structure evolution and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Hongying Yang (Chemical Engineering Journal, 2026)

Identification of functional hotspots via hybrid nuclear magnetic Resonance-Computational strategy for directed evolution of large enzymes - Yihao Chen; Zhou Gong; Xiaoling Zhao; Ali Raza; Mingjun Zhu; Zhiqing Tao; Wenhui Li; Xu Zhang; Maili Liu; Lichun He (Bioresource Technology, 2026)

Mechanistic Insight into Formation and Release Enhancement of Sulindac-Amino Acid Small-Molecule Hydrogels - Jiaxin Chen; Huizhen Sun; Wuheng Yue; Zhimin Yue; Baimin Niu; Mingjun Li; Xinru Lu; Jue Wang; Xiaoqian Liu; Jiawei Han (Pharmaceutical Research, 2026)

PRSS23 functions downstream of ZEB1 to promote esophageal squamous cell carcinoma progression by driving M2 polarization of tumor associated macrophages - Wei Chen; Chanjuan Chen; Zhongyun Hu; Fanfan Li; Yao Peng; Mingjun Zhang (Molecular and Cellular Biochemistry, 2026)

Hydrate stability assessment in marine environments: Implications for CO2 sequestration site optimization - Lei Zhang; Wei Song; Fei Huang; Bingbing Chen; Huiru Sun; Mingjun Yang (Journal of Environmental Chemical Engineering, 2026)

Quality deterioration and metabolic regulation during hot-air drying of Rheum palmatum L.: an integrated analysis of physiology, drying kinetics, non-targeted metabolomics, and enzyme activity dynamics - Wen Luo; Yingying Chen; Jia Zhou; Mingjun Yang; Yonggang Wang (Physiology and Molecular Biology of Plants, 2026)

Recent advances on aroma characteristics of fruit wine: analytical techniques, formation mechanisms and aroma-enhancement brewing technology - Mingjun Jiang; Zhenbao Shi; Ziqiang Chen; Jinglong Zhang; Jian Lu; Dianhui Wu (Critical Reviews in Food Science and Nutrition, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Conversion of wheat straw by black soldier fly larvae and fertilization effects of frass - Xifeng Wang; Ruohan Wang; Junzhao Wei; Rui Hu; Ziling Wang; Haifeng Li; Pengxiao Chen; Jianhang Qu; Mingjun Li (Journal of Asia-Pacific Entomology, 2026)

A high-accuracy stacking model for automatic identification of aeolian saltating tracks in high-speed pictures - Mengjie Pu; Fanmin Mei; Chuan Lin; Mingjun Sui; Hongda Chen; Shenyang He; Weikai Wang; Chang Zhou; Jin Su; Jinguang Chen (Aeolian Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

CO2 injection strategies to enhance the sequestration capacity in oceanic reservoir for hydrate-based carbon storage - Xinru Wang; Jing Chen; Huiru Sun; Bingbing Chen; Xin Lv; Weixin Pang; Yongchen Song; Mingjun Yang (Fuel, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

The promising effects of bacterial and microalgal inoculants in enhancing tomato growth and improving soil quality - Tongtong Xu; Qixiang Xian; Yunqian Cui; Huali Pei; Wei Liu; Mingjun Chen; Jingling Liu; Hongbo Yu; Nortoji A. Khujamshukurov; Meimei Wu (Biocatalysis and Agricultural Biotechnology, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Revealing trapping effects of soil components on oil during the thermal desorption process of petroleum-contaminated soils - Haohao Bian; Shuaiyu Chen; Junhao Huang; Zixuan Zhang; Mingjun Wu; Wei Zhang; Sher Bahadar Khan; Xintai Su (Chemical Engineering Journal, 2026)

Stability assessment of CO2 hydrate-based sequestration in complex marine environments - Lei Zhang; Heng Liu; Xinyi Shan; Bingbing Chen; Mingjun Yang (Chemical Engineering Journal, 2026)

Glacier and glacial lake evolution in response to local climate forcing: A quantitative assessment in Ulugh Muztagh, Eastern Kunlun Mountains - Lihua Chen; Yanjun Che; Yun Cao; Mingjun Zhang; Lailei Gu; Shijin Wang (Cold Regions Science and Technology, 2026)

Optimal monitoring time of kiwifruit orchard soil moisture content under irrigation using the red-edge indices acquired by UAV-based mutilspectral data - Mingjun Wang; Shidan Zhu; Shouzheng Jiang; Fei Chen; Xiuyun Yu; Lu Zhao; Zongjun Wu; Quanshan Liu; Ningbo Cui; Zhihui Wang; Liwen Xing (Computers and Electronics in Agriculture, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Disclosing occurrence of typical tire wear particle-derived chemicals in grassland soils from remote pastoral areas, north China - Guoguang Wang; Aoduo Yang; Shuaihao Liu; Mingjun Mo; Haiyue Chen; Guangzhi Rong; Haixia Wang; Yu Liu (Environmental Research, 2025)

CTAB-mediated in situ synthesis of schwertmannite for enhanced As(V) removal from arsenic-contaminated wastewater: performance and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Zhenan Jin; Hongying Yang (Chemical Engineering Journal, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

Multifunctional scaffolds based on 3D printing for spinal cord and peripheral nerve defect repair - Xinran Chen; Mingjun Wu; Jie Zhang; Pengxiang Yang; Jiahui Guo; Xiaosong Gu; Xiu Dai (Chemical Engineering Journal, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Investigating the regulatory role of seasonal changes in soil and microbial communities on Codonopsis pilosula physiology - Ning Zhu; Yumeng Zhou; Mingjun Yang; Feifan Leng; Xiaoxu Lv; Jixiang Chen; Wen Luo; Yonggang Wang (Biocatalysis and Agricultural Biotechnology, 2025)

Novel T–U-Shaped Barge Design and Dynamic Response Analysis for Float-Over Installation of Offshore Converter Platform - Ping Li; Li Zhao; Mingjun Ouyang; Kai Ye; Rui Zhao; Meiyan Zou; Mingsheng Chen (Journal of Marine Science and Engineering, 2025)
To address the current lack of specialized equipment for offshore wind platform installation and the unresolved challenges in deploying large offshore converter stations, this paper proposes a novel T–U-shaped barge for large offshore wind structures. First, a hydrodynamic model of the T–U-shaped barge is constructed and analyzed in ANSYS-AQWA. The influence of resonance occurring in the gap at the U-shaped stern on the frequency-domain model of the T–U-shaped barge is investigated. Subsequently, two installation configurations are examined: loading at the bow and loading at the stern of the T–U-shaped barge. This study comprehensively considers key components of the float-over installation system, including leg mating units (LMUs), deck support units (DSUs), fenders, and mooring cables. The results show that, for both installation schemes, the dynamic load distribution on each LMU evolves as the load-transfer stage progresses, and the sensitivity to wave period varies across different load-transfer stages, even under the same operating condition. This study evaluates the performance of the proposed T–U-shaped barge in the float-over installation of large offshore converter stations, demonstrating that its distinctive configuration endows it with strong functionality and provides valuable references for optimizing offshore wind-structure installation methods, as well as for the design and manufacturing of installation equipment.

Study on the enterprise property rights differences of Porter hypothesis effect of environmental protection tax - Guodong Wang; Jianya Zhou; Mingjun Chen (Environment, Development and Sustainability, 2025)

Observer-Based Robust Control for Dynamic Positioning in Float-Over Installation of Offshore Converter Stations - Ping Li; Li Zhao; Mingjun Ouyang; Jinghao Zhao; Rui Zhao; Meiyan Zou; Mingsheng Chen (Journal of Marine Science and Engineering, 2025)
With the development of offshore wind power progressing towards larger-scale and deeper-water projects, the float-over installation of offshore converter stations has become a mainstream solution due to its high carrying capacity, efficiency and cost-effectiveness. This study addresses the dynamic positioning (DP) challenges during this operation, where traditional PID controllers often struggle with performance under complex environmental loads. An Observer-Based Robust Controller (OBRC) is proposed and integrated with a constant parameter time-domain model (CPTDM) to simulate the DP process of a novel T-U barge. Time-domain simulations for both standby and entry phases were conducted under various wave directions and periods. The results demonstrate that the OBRC significantly outperforms the conventional PID controller in maintaining positioning accuracy. The findings provide critical insights into motion responses and control strategies, offering valuable guidance for the design and safe operation of future float-over installations.

Synchronous removal of heavy metals and ammonia-nitrogen by magnesium ammonium phosphate (MAP)-enhanced microbial induced calcite precipitation (MICP) - Lin Li; Huaji Sun; Chongyang Ren; Ziyi Zhao; Yueteng Song; Mingjun Wang; Shuiquan Chen; Gang Zhou (Journal of Hazardous Materials, 2025)

From stainless steel to batteries: industrial-scale closed-loop hydrometallurgical integration for ferronickel-to-precursor conversion - Jun Luo; Pengfei Yang; Jing Chen; Yanhu Chen; Mingjun Rao; Guanghui Li; Tao Jiang (Journal of Cleaner Production, 2025)

Microplastics and nanoplastics across the food web: Challenges and mitigation strategies in securing human health - Mingjun Chen; Ali Raza Khan; Muhammad Sohail Memon; Babar Iqbal (Process Safety and Environmental Protection, 2025)

Molecular simulation insights into methane-water adsorption and transport mechanisms in deep shale multiscale Nanoslits under high-temperature and high-pressure conditions - Yeyu Zou; Mingjun Chen; Yili Kang; Lijun You; Peisong Li; Xueni Chen; Fan Zhang (Fuel, 2025)

Enhanced mineralization and dust suppression mechanism of Bacillus pasteurii synergized with Bacillus mucilaginosus capable of CO2 capture effect - Gang Zhou; Ziyi Zhao; Guoqing Zhang; Xiao Gao; Mingjun Wang; Bo Wei; Xi Chen; Jihua Li; Lin Li (Chemical Engineering Journal, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Thermodynamic and kinetic studies of CO2 hydrate stability in complex deep-oceanic environments - Lei Zhang; Ziming Yang; Yang Ge; Bingbing Chen; Huiru Sun; Yongchen Song; Mingjun Yang (Process Safety and Environmental Protection, 2025)

Study on the self-regeneration strategy of aged asphalt based on magnetic response controlled release microcapsules: A new sustainable self-regenerating pavement system - Yufeng Tian; Lei Xu; Daquan Sun; Hangtian Ni; Zhongbo Chen; Jianxiang Guo; Mingjun Hu (Journal of Cleaner Production, 2025)

Experimental studies on the correlations of male respiratory parameters with their body composition - Yi Xu; Lijuan Wang; Haitang Liu; Mingming Zhai; Mingjun Zhang; Haiguo Yin; Minzhou Chen (Energy and Buildings, 2025)

Water-in-eutectogel electrolytes for scalable solid-state electrochromic devices - Jianbo Deng; Mingjun Chen; Xiang Zhang; Hulin Zhang; Liping Hu; Shuokun Sun; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

In situ constructing artificial interfacial layer enables dendrite-free zinc anode in aqueous batteries - Canglong Li; Changding Wang; Jie Huang; Qiwen Zhao; Wen Liu; Yuxuan Song; Mingjun Rao; Fu Wan; Yuejiao Chen; Weigen Chen; Shuhui Sun (Chemical Engineering Journal, 2025)

The role of clay in hydrate-based carbon emission reduction: Phenomenon, mechanisms, and application - Huiquan Liu; Shuai Wang; Yixuan Fu; Changrui Shi; Yongchen Song; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

A rapid and visual detection method for Alternaria alternata, the causal agent of leaf spot disease on yam, based on RPA-CRISPR/Cas12a - Yulong He; Chenwei Tong; Huixuan Chen; Weichao Zhao; Liping Zhan; Ruifei Wang; Jiangli Zhang; Jin Gao; Chaochuang Li; Mingjun Li; Qingxiang Yang (Physiological and Molecular Plant Pathology, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Impact of sewage sludge biochar spheres as constructed wetland substrates on antibiotic removal and application - Mingjun Zhong; Ze Zhang; Jialiang Zhang; Zihao Luo; Yunxian Chen; Mengxue Liu; Beini Gong; Hongcan Cui; Lihua Cui (Journal of Environmental Management, 2025)

Monolithic and effective kinetic promoter formed by immobilizing MWCNTs on cellulose for efficient hydrate-based gas storage - Shuai Wang; Huilian Sun; Zhen Li; Changrui Shi; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2025)

Investigation of water blocking mitigation in a normal-pressure shale gas reservoir by high-temperature treatment: Insights from heat transfer range - Mingjun Chen; Xueni Chen; Yili Kang; Zheng Cheng; Lijun You; Gang Xiong; Dongsheng Yang; Chaozhong Qin (Fuel, 2025)

Rapid formation of carbon dioxide hydrate governed by the natural nano-clay for effective carbon dioxide capture - Huiquan Liu; Shuai Wang; Changrui Shi; Yongchen Song; Yixuan Fu; Zhen Li; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Oxidation and nitrosation in Cantonese sausage during processing and storage-The impact of adding Prunus mume polyphenol - Jingrong Cheng; Peiyu Chen; Xueming Liu; Daobang Tang; Huaigu Yang; Mingjun Zhu (Food Control, 2025)

Characterization and functional analysis of small heat shock protein gene HSP20.1 in Bombyx mandarina - Hui An; Jiaqi Ding; Enxi Chen; Ruonan Li; Mingjun Lin; Heying Qian; Guodong Zhao (International Journal of Tropical Insect Science, 2024)

The peculiar role of iodides and formation of iodinated oligomer byproducts upon phenol mineralization with boron-doped diamond anode - Ruochen Liu; Mingjun Ouyang; Shujuan Chen; Saier Wang; Chenwei Liu; Chunyong Zhang; Hua Wu (Chemical Engineering Journal, 2024)

Exploration of the Formation Mechanism of Underground Brine Based on Hydrodynamic Environment Analysis Using Grain-Size Data of One Drilling Core - Qiao Su; Ying Yu; Mingjun Chen; Tengfei Fu; Wenzhe Lyu; Wenquan Liu (Journal of Marine Science and Engineering, 2024)
The Laizhou Bay area in China harbors a significant amount of Quaternary brine resources, which have been gradually depleted due to intensive long-term exploitation. It is widely accepted that underground Quaternary brine in Laizhou Bay originates from seawater. However, there are disputes regarding the specific form of seawater concentration and the geological processes leading to brine formation. Revealing the genesis of shallow brine in different geological environments is of great scientific significance for resource production and environmental protection. This study analyzed the hydrodynamic conditions of underground brine and adjacent strata based on grain size data, and the possible formation mechanisms of brine layers at different depths were discussed. The mineralization of underground brine is a complex process controlled by various factors, such as specific meteorological and paleogeographic environments, topography, and hydrogeological conditions. On the southern coast of Laizhou Bay, there are three ways in which underground brine layers are formed: residual evaporation from lagoons during the initial regression stage, the hypersaline zone in estuarine lagoons during high-sea-level periods, and brine formation from seawater evaporation on intertidal flats. Turbulent sea–land interactions and the development of river deltas are also necessary conditions for brine mineralization, as they are favorable for replenishing, transporting, and storing underground brine layers.

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Behaviors of hydrate cap formation via CO2-H2O collaborative injection:Applying to secure marine carbon storage - Mingjun Yang; Mingyu Wu; Ziming Yang; Pengfei Wang; Bingbing Chen; Yongchen Song (Gas Science and Engineering, 2024)

Spatiotemporal distribution characteristics of fracturing fluid in multiscale pore structure of deep marine shale gas reservoirs - Peisong Li; Mingjun Chen; Yili Kang; Hua Liu; Sidong Fang; Lijun You; Zhehan Lai; Yeyu Zou (Fuel, 2024)

Boosting oxygen reduction reaction kinetics by Fe–V dual sites in ultrafine V-Fe3C nanoparticles for aluminum-air batteries - Shuya Zhang; Qiming Chen; Qianqiao Wang; Xinyu Luo; Mingjun Cen; Wenchao Peng; Yang Li; Qicheng Zhang; Xiaobin Fan (Chemical Engineering Journal, 2024)

Defective carbon-bridged Cu sites to boost oxygen reduction reaction in neutral zinc-air batteries - Tianjing Wu; Honghui Hu; Yufeng Wu; Mingjun Jing; Zhanpeng Chen; Fang Chen; Yansong Bai; Dan Li; Sheng Zhang; Lijie Liu; Wentao Deng; Hongshuai Hou; et al. (Chemical Engineering Journal, 2024)

Scalable MXene/Sepiolite film-based hydrovoltaic generators with outstanding output power - Weijing Yuan; Huiquan Liu; Yixuan Fu; Yang Zhang; Haoqi Huo; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

Grifola frondosa polysaccharide's therapeutic potential in oxazolone-induced ulcerative colitis - Xiaoyi Liu; Mingjun Zhang; Shuai Chen; Huijuan Liu; Haoran Ma; Ting Hu; Peng Luo; Shaofeng Wei (Carbohydrate Polymers, 2024)

MicroRNA-specific therapeutic targets and biomarkers of apoptosis following myocardial ischemia–reperfusion injury - Teng Ge; Bo Ning; Yongqing Wu; Xiaolin Chen; Hongfei Qi; Haifang Wang; Mingjun Zhao (Molecular and Cellular Biochemistry, 2024)

Dynamic patterns of particulate matter concentration and size distribution in urban street canyons: insights into diurnal and short-term seasonal variations - Xiaoshuang Wang; Xiaoping Chen; Zhixiang Zhou; Mingjun Teng; Yang Xiang; Chucai Peng; Chunbo Huang; Changhui Peng (Environmental Monitoring and Assessment, 2024)

Synthesis, Structure and Luminescence Properties of Mn-doped MgAl2O4 Red-Emitting Phosphors with Varying Sintering Temperature - Jiahao Zha; Chongjun He; Fangzhou Chen; Hongwei Wang; Biao Dong; Lijuan Liu; Mingjun Xia; Chenguang Deng; Qian Li; Yuangang Lu; Huiting Chen (Journal of Fluorescence, 2024)

Liquidizing crystal MIL-100(Fe) to coating silica powder for purifying wastewater - Shiyong Wei; Aijia Cao; Siyuan Huang; Yao Shen; Ting Lei; Songmei Luo; Mingjun Cai; Wenjun Xiang; Anying Chen; Rui Wang (Chemical Engineering Journal, 2024)

Bimetallic porphyrin PET radiotracers for Low-Dose MRI contrast enhancement - Chen Xie; Xiong Li; Leilei Zhang; Ho-Fai Chau; Waygen Thor; Wing Sze Tam; Benjamin Woolley; Mingjun Jiang; Chi-Fai Ng; Mauro Botta; Tao Zhang; Nicholas J. Long; et al. (Chemical Engineering Journal, 2024)

Copper induces cytotoxicity in freshwater bivalve Anodonta woodiana hemocytes - Mingjun Yan; Xiubao Chen; Tao Jiang; Junren Xue; Karsten Liber; Hongbo Liu; Jian Yang (Chemosphere, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Depositional process and sediment dispersal pattern of mass transport complex on a slope with numerous elliptical depressions, northwestern South China Sea - Chao Liang; Chiyang Liu; Xinong Xie; Xiaohang Yu; Lei Huang; Jie Pan; Yunlong He; Hui Chen; Dongmei Tian; Honggang Mi; Mingjun Li; Hui Zhang (Sedimentary Geology, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Enhancing precision of root-zone soil moisture content prediction in a kiwifruit orchard using UAV multi-spectral image features and ensemble learning - Shidan Zhu; Ningbo Cui; Li Guo; Huaan Jin; Xiuliang Jin; Shouzheng Jiang; Zongjun Wu; Min Lv; Fei Chen; Quanshan Liu; Mingjun Wang (Computers and Electronics in Agriculture, 2024)

The efficient uptake of uranium by amine-functionalized β-cyclodextrin supported fly ash composite from polluted water - Congcong Chen; Xuan Liu; Xiaoyu Tian; Jiaqi Feng; Yujia Liu; Mingjun Song; Wenkun Zhu; Yong Zhang (Science of The Total Environment, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

Treatment of landfill leachate by black soldier fly (Hermetia illucens L.) larvae and the changes of intestinal microbial community - Mingjun Ruan; You Li; Chong Ma; Yingying Xie; Wenying Chen; Limei Luo; Xueling Li; Wenfeng Hu; Bin Hu (Journal of Environmental Management, 2024)

Effect of various phosphorus levels on the extraction of Cd, the transformation of P, and phosphorus-related gene during the phytoremediation of Cd contaminated soil - Hongli Huang; Rule Zhao; Guanlin Guo; Yinhai He; Shuofu Chen; Yichun Zhu; Mingjun Xiao; Ping Liu; Junwu Liu; Yingchun Fang; Yaoyu Zhou (Environmental Research, 2024)

Corrigendum to “The right tree for the right street canyons: An approach of tree species selection for mitigating air pollution” [Build. Environ. 245C (2023) 110886] - Yayun Guo; Qiankun Xiao; Chen Ling; Mingjun Teng; Pengcheng Wang; Zhiyan Xiao; Changguang Wu (Building and Environment, 2024)

Reconstruction of Historical Metal Backgrounds in Lacustrine Environments of China Using an Anodonta woodiana “Specimen Bank” - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Degradation of petroleum hydrocarbon contaminants by Rhodococcus erythropolis KB1 synergistic with alfalfa (Medicago sativa L.) - Yan Nan; Ning Zhu; Shangchen Sun; Tianzhu Lei; Xiaopeng Guo; Feifan Leng; Mingjun Yang; Jixiang Chen; Yonggang Wang (Environmental Science and Pollution Research, 2024)

Analysis of the wet-towing operation of a semi-submersible floating wind turbine using a single tugboat - Mingsheng Chen; Yingjie Chen; Tingqiu Li; Yichang Tang; Jun Ye; Hao Zhou; Mingjun Ouyang; Xianxiong Zhang; Wei Shi; Xinghan Sun (Ocean Engineering, 2024)

Spatio-temporal characteristics of farmland occupation of construction land expansion and its spatial relationship with grain yield in China for 2000–2020 - Zihua Li; Mingjun Ding; Kun Xie; Jingru Li; Liwen Chen (Journal of Geographical Sciences, 2024)

Enhancing tetracycline degradation with biomass carbon quantum dot (CQDs)-modified magnetic heterojunction CeO2-Fe3O4 under visible light - Hua Chai; Ze Zhang; Jie Sun; Mingjun Zhong; Mengxue Liu; Jing Li; Zihao Chen; Beini Gong; Qiaoling Xu; Zhujian Huang; Lihua Cui (Journal of Environmental Chemical Engineering, 2024)

A fully coupled time domain model capturing nonlinear dynamics of float-over deck installation - Mingsheng Chen; Meiyan Zou; Ling Zhu; MingJun Ouyang; Qiyu Liang; Wenhua Zhao (Ocean Engineering, 2024)

Application of bacterial agent YH for remediation of pyrene-heavy metal co-pollution system: Efficiency, mechanism, and microbial response - Yuhua Su; Mingjun Zhu; Hang Zhang; Hongxu Chen; Jiguo Wang; Chaocheng Zhao; Qiyou Liu; Yingying Gu (Journal of Environmental Management, 2024)

Copper Stress Causes Shell Morphology Changes in Early Juvenile Anodonta woodiana Based on Geometric–Morphometric Analysis - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Tao Jiang; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Effects of dominant plant species change on soil multifunctionality in alpine meadows of the three-river source region - Liwen Chen; Mingjun Ding; Hua Zhang; Nengyu Wang; Yueju Zhang; Jiayi Wan; Kun Xie (Journal of Cleaner Production, 2024)

Achieving tunable time-dependent delayed emission color via dynamic competition between the matrix and carbon dots for anti-counterfeiting and multidimensional encryption - Yufeng Chang; Nian Fu; Mingjun Chen; You Zhang; Fuxing Li; Zhenyang Liu; Fenghe Wang; Gang Yue; Xu Li; Li Guan (Chemical Engineering Journal, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Numerical modelling of a catamaran float-over deck installation for a spar platform with complex hydrodynamic interactions and mechanical couplings - Mingsheng Chen; Mingjun Ouyang; Tingqiu Li; Meiyan Zou; Jun Ye; Xinliang Tian (Ocean Engineering, 2023)

Does green finance promote low-carbon economic transition? - Mingjun Hu; Zhengling Sima; Shiyu Chen; Minmin Huang (Journal of Cleaner Production, 2023)

The right tree for the right street canyons: An approach of tree species selection for mitigating air pollution - Yayun Guo; Qiankun Xiao; Chen Ling; Mingjun Teng; Pengcheng Wang; Zhiyan Xiao; Changguang Wu (Building and Environment, 2023)

Rapid Detection of blaKPC in Carbapenem-Resistant Enterobacterales Based on CRISPR/Cas13a - Mingjun Liang; Bin Xiao; Lidan Chen; Xiaoyan Huang; Jinchao Li; Zhenzhan Kuang; Xinping Chen; Xiuna Huang; Zhaohui Sun; Linhai Li (Current Microbiology, 2023)
Klebsiella pneumoniae carbapenemase (KPC) is a crucial enzyme that causes carbapenem resistance in Enterobacterales , and infections by these "superbugs" are extremely challenging to treat. Therefore, there is a pressing need for a rapid and accurate KPC detection test to control the prevalence of carbapenem-resistant Enterobacterales (CREs). In this study, we established a novel method for detection of bla KPC , the gene responsible for encoding KPC, based on a recombinase polymerase amplification (RPA) and a CRISPR/Cas13a reaction coupled to fluorophore activation (termed RPA-Cas13a assay). We carefully selected a pair of optimal amplification primers for bla KPC and achieved a lower limit of detection of approximately 2.5 copies/μL by repeatedly amplifying a recombinant plasmid containing bla KPC . The RPA-Cas13a assay demonstrated a sensitivity of 96.5% and specificity of 100% when tested on 57 bla KPC -positive CRE strains, which were confirmed by DNA sequencing. Moreover, in 311 sputum samples, the theoretical antibiotic resistance characteristics of bla KPC -positive strains obtained by the RPA-Cas13a assay were highly consistent with the results of antibiotic susceptibility test ( Kappa = 0.978 > 0.81, P < 0.01). In conclusion, the RPA-Cas13a system is a simple and one-hour efficient technology for the detection of a potentially fatal antibiotic resistance gene.

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

Continuous measurement of gas permeability in non-homogeneous hydrate reservoirs under effective pressure via a novel apparatus - Guangjun Gong; Guojun Zhao; Weixin Pang; Mengru Tian; Bingbing Chen; Mingjun Yang; Yongchen Song (Gas Science and Engineering, 2023)

Investigation of LncRNA PVT1 and MiR-21-5p Expression as Promising Novel Biomarkers for Autism Spectrum Disorder - Mingjun Jiang; Guanwen Chen (Journal of Molecular Neuroscience, 2023)

SARS-COV-2 spike protein promotes RPE cell senescence via the ROS/P53/P21 pathway - Yuhang Zhang; Xuyan Peng; Mengjiao Xue; Jingjing Liu; Guohui Shang; Mingjun Jiang; Dandan Chen; Baixue Liu; Yuxuan Wang; Xiaolin Jia; Jianqing Xu; Fengyan Zhang; et al. (Biogerontology, 2023)
SARS-Cov-2 infection, which has caused the COVID-19 global pandemic, triggers cellular senescence. In this study, we investigate the role of the SARS-COV-2 spike protein (S-protein) in regulating the senescence of RPE cells. The results showed that administration or overexpression of S-protein in ARPE-19 decreased cell proliferation with cell cycle arrest at the G1 phase. S-protein increased SA-β-Gal positive ARPE-19 cells with high expression of P53 and P21, senescence-associated inflammatory factors (e.g., IL-1β, IL-6, IL-8, ICAM, and VEGF), and ROS. Elimination of ROS by N-acetyl cysteine (NAC) or knocking down p21 by siRNA diminished S-protein-induced ARPE cell senescence. Both administrated and overexpressed S-protein colocalize with the ER and upregulate ER-stress-associated BIP, CHOP, ATF3, and ATF6 expression. S-protein induced P65 protein nuclear translocation. Inhibition of NF-κB by bay-11-7082 reduced S-protein-mediated expression of senescence-associated factors. Moreover, the intravitreal injection of S-protein upregulates senescence-associated inflammatory factors in the zebrafish retina. In conclusions, the S-protein of SARS-Cov-2 induces cellular senescence of ARPE-19 cells in vitro and the expression of senescence-associated cytokines in zebrafish retina in vivo likely by activating ER stress, ROS, and NF-κb. These results may uncover a potential association between SARS-cov-2 infection and development of AMD.

Bioinspired polydopamine nanosheets for the enhancement in anti-corrosion performance of water-borne epoxy coatings - Mingjun Cui; Xinyu Chen; Shixiang Mei; Siming Ren (Chemical Engineering Journal, 2023)

CO2 capture performance of CaO-based sorbent modified with torrefaction condensate during calcium looping cycles - Chongcong Li; Xingli Gong; Hao Zhang; Yan Zhang; Mingjun Yang; Bingbing Chen (Chemical Engineering Journal, 2023)

EIF4A3-Induced Exosomal circLRRC8A Alleviates Granulosa Cells Senescence Via the miR-125a-3p/NFE2L1 axis - Jie Xing; Mengxue Zhang; Shijie Zhao; Mingjun Lu; Li Lin; Lu Chen; Wujiang Gao; Wenxin Li; Junyu Shang; Jiamin Zhou; Xiaolan Zhu (Stem Cell Reviews and Reports, 2023)
Premature ovarian failure (POF) is an important cause of female infertility and seriously impacts the physical and psychological health of patients. Mesenchymal stromal cells-derived exosomes (MSCs-Exos) have an essential role in the treatment of reproductive disorders, particularly POF. However, the biological function and therapeutic mechanism of MSCs exosomal circRNAs in POF remain to be determined. Here, with bioinformatics analysis and functional assays, circLRRC8A was found to be downregulated in senescent granulosa cells (GCs) and acted as a crucial factor in MSCs-Exos for oxidative damage protection and anti-senescence of GCs in vitro and in vivo. Mechanistic investigations revealed that circLRRC8A served as an endogenous miR-125a-3p sponge to downregulate NFE2L1 expression. Moreover, eukaryotic initiation factor 4A3 (EIF4A3), acting as a pre-mRNA splicing factor, promoted circLRRC8A cyclization and expression by directly binding to the LRRC8A mRNA transcript. Notably, EIF4A3 silencing reduced circLRRC8A expression and attenuated the therapeutic effect of MSCs-Exos on oxidatively damaged GCs. This study demonstrates a new therapeutic pathway for cellular senescence protection against oxidative damage by delivering circLRRC8A-enriched exosomes through the circLRRC8A/miR-125a-3p/NFE2L1 axis and paves the way for the establishment of a cell-free therapeutic approach for POF. CircLRRC8A may be a promising circulating biomarker for diagnosis and prognosis and an exceptional candidate for further therapeutic exploration. Graphical Abstract

How can blockchain technology promote food safety in agricultural market?—an evolutionary game analysis - Yanhu Bai; Zhuodong Yang; Minmin Huang; Mingjun Hu; Shiyu Chen; Jianli Luo (Environmental Science and Pollution Research, 2023)

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Efficient removal of iron during partial neutralization of nickel laterite acid leach solution: DFT calculation and experimental verification of mechanism - Changye Mang; Guanghui Li; Yanhu Chen; Jun Luo; Mingjun Rao; Tao Jiang (Hydrometallurgy, 2023)

A hybrid DEMATEL-COPRAS method using interval-valued probabilistic linguistic term set for sustainable hydrogen fuel cell supplier of new energy vehicles - Qinghua Mao; Jinjin Chen; Jian Lv; Mengxin Guo; Mingjun Tian (Environmental Science and Pollution Research, 2023)

A Coupled Hydrodynamic–Structural Model for Flexible Interconnected Multiple Floating Bodies - Mingsheng Chen; Mingjun Ouyang; Hongrui Guo; Meiyan Zou; Chi Zhang (Journal of Marine Science and Engineering, 2023)
Evaluating the structural safety and seakeeping performance of very large floating structures (VLFS) using the rigid module flexible connector (RMFC) method remains challenging due to the complexity of the coupled hydrodynamic–structural responses in this system. In this study, a coupled hydrodynamic–structural frequency–time domain model is developed based on the RMFC method employing the planar Euler–Bernoulli beam elements to investigate the dynamic responses of multi-module floating systems. To reveal the dynamic characteristics of the systems, the coupled hydrodynamic–structural responses are investigated using a frequency–time-domain numerical model with viscous correction, in which the mass and stiffness attributes of connectors are incorporated into the system. Given the effects of hydrodynamic interaction, consideration is given to the case of three modular boxes connected by flexible beams aligned in series in shallow water to validate the present model. Higher efficiency and accuracy can be found in the system using viscous correction in potential flow theory and introducing state–space model to replace the convolution terms in the Cummins equation for the time domain. Moreover, this model can be extended to a considerable number of floating modules, which provides possibilities to analyze N-module floating systems.

Atmospheric acid leaching of powdery Ni-Co-Fe alloy derived from reductive roasting of limonitic laterite ore and recovery of battery grade iron phosphate - Mingjun Rao; Jing Chen; Tao Zhang; Meishi Hu; Jinxiang You; Jun Luo (Hydrometallurgy, 2023)

Effects of molecular structure and functional groups on the performance of carbonyl organic compounds as cathodes for aluminum batteries - Gaohong Wu; Mingjun Chen; Wenrong Lv; Xiaoxu Wang; Wenming Zhang; Zhanyu Li (Chemical Engineering Journal, 2023)

Experimental study on the effect of salt crystallization on multi-scale transportation of shale gas - Jiaxin Shao; Lijun You; Na Jia; Yili Kang; Mingjun Chen; Zhiwei Hao (Gas Science and Engineering, 2023)

Dual effects of retained fracturing fluid on methane diffusion in shale containing adsorbed methane - Jiajia Bai; Yili Kang; Mingjun Chen; Zhangxin Chen; Lei Tao; Na Zhang; Wenyang Shi; Qingjie Zhu (Gas Science and Engineering, 2023)

Investigation of induced change in pore structure by the reaction of shale with fracturing fluid - Jiaxin Shao; Lijun You; Na Jia; Yili Kang; Mingjun Chen (Gas Science and Engineering, 2023)

Molecular-micron multiscale toughening and flame retarding for polyurethane foams - Furong Zeng; Xiaofeng Men; Mingjun Chen; Bowen Liu; Qingwen Han; Shengchao Huang; Haibo Zhao; Yuzhong Wang (Chemical Engineering Journal, 2023)

Synthesis and enhancement of carbon quantum dots from Mopan persimmons for Fe3+ sensing and anti-counterfeiting applications - Haotian Ma; Li Guan; Mingjun Chen; You Zhang; Yue Wu; Zhenyang Liu; Dawei Wang; Fenghe Wang; Xu Li (Chemical Engineering Journal, 2023)

A multi-criteria group decision-making framework for investment assessment of offshore floating wind-solar-aquaculture project under probabilistic linguistic environment - Qinghua Mao; Mengxin Guo; Jian Lv; Jinjin Chen; Mingjun Tian (Environmental Science and Pollution Research, 2023)

Hydrogen sulfite promoted the activation of persulfate by μM Fe2+ for bisphenol A degradation - Shiyao Chen; Caixia Yan; Minghua Nie; Leliang Wu; Mingjun Ding; Peng Wang (Environmental Science and Pollution Research, 2022)

Host Fish Suitability for Freshwater Bivalve Anodonta woodiana Breeding Programs - Xiubao Chen; Guochao Duan; Mingjun Yan; Hongbo Liu; Tao Jiang; Jian Yang (Fishes, 2022)
The freshwater bivalve Anodonta woodiana is native to China and widely distributed in Asia, Europe, and North America. However, natural populations of A. woodiana in China have dramatically declined recently. Several fish species have been used as potential hosts in breeding programs; nonetheless, the optimal host species is yet to be identified. In this study, we examined the suitability of five potential host fish species (bighead carp, common carp, crucian carp, yellow catfish, and tilapia) for A. woodiana under laboratory conditions. No significant difference was found in the number of glochidia attached to the five fish species; however, tilapia hosted more transformed juveniles than bighead carp, common carp, or yellow catfish (p

The Mitochondrial-Derived Peptide MOTS-c Attenuates Oxidative Stress Injury and the Inflammatory Response of H9c2 Cells Through the Nrf2/ARE and NF-κB Pathways - Caijie Shen; Jian Wang; Mingjun Feng; Jianye Peng; Xiangfeng Du; Huimin Chu; Xiaomin Chen (Cardiovascular Engineering and Technology, 2022)

Ameliorating Inflammation in Insulin-resistant Rat Adipose Tissue with Abdominal Massage Regulates SIRT1/NF-κB Signaling - Tianjiao Gao; Shaotao Chen; Yiran Han; Dongmei Zhang; Yi Tan; Yutao He; Mingjun Liu (Cell Biochemistry and Biophysics, 2022)
It was the aim of this study to determine whether abdominal massage reverses high-fat diet-induced insulin resistance compared with RSV treatment. A total of sixty male Sprague-Dawley rats were randomly placed in one of four groups:the non-fat diet (NFD), the high-fat diet (HFD), the HFD with abdominal massage (HFD+ AM), and the HFD plus resveratrol (HFD+ RSV). For eight weeks, rats were fed high-fat diets to create insulin resistance, followed by six weeks of either AM or RSV. Molecular mechanisms of adipogenesis and cytokine production in rats with high-fat diets were investigated. The model rat adipose tissue showed significant improvements in obesity, glucose intolerance, and the accumulation of lipid in the body [the total cholesterol level (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C)], metabolic effects of glucose [The fasting blood glucose (FBG), Fasting insulin levels (FINS)], inflammatory status [interleukin-6 (IL-6) and tumor necrosis factor (TNF)-α, C-reactive protein (CRP)], and macrophage polarization after AM or RSV treatment. Further, AM increased SIRT1/NF-κB signaling in rat adipose tissue. Accordingly, in rat adipose tissue, our results indicate that AM regulates the secretion of proinflammatory cytokines, blood sugar levels, and related signaling pathways, contributing to improvement of IR, which may serves as a new therapeutic approach for the treatment for IR.

Carbon emission efficiency and spatio-temporal dynamic evolution of the cities in Beijing-Tianjin-Hebei Region, China - Li-Ming Xue; Zhi-Xue Zheng; Shuo Meng; Mingjun Li; Huaqing Li; Ji-Ming Chen (Environment, Development and Sustainability, 2022)

DVPred: a disease-specific prediction tool for variant pathogenicity classification for hearing loss - Fengxiao Bu; Mingjun Zhong; Qinyi Chen; Yumei Wang; Xia Zhao; Qian Zhang; Xiarong Li; Kevin T. Booth; Hela Azaiez; Yu Lu; Jing Cheng; Richard J. H. Smith; et al. (Human Genetics, 2022)

Velocity analysis of noisy seismic data based on RSVD weighted semblance - Yankai Xu; Siyuan Cao; Xiao Pan; Siyuan Chen; Mingjun Cai; Jialiang Zhang (Studia Geophysica et Geodaetica, 2022)

Abdominal Massage Alleviates Skeletal Muscle Insulin Resistance by Regulating the AMPK/SIRT1/PGC-1α Signaling Pathway - Yiran Han; Zeyuan Lu; Shaotao Chen; Chongwen Zhong; Minghui Yan; Heran Wang; Meng Meng; Mingjun Liu (Cell Biochemistry and Biophysics, 2021)
Abdominal massage (AM), a traditional Chinese medicine-based treatment method, has received considerable attention in the recent years. The aim of the present study was to investigate the effect of AM on high-fat diet (HFD)-induced insulin resistance (IR) in comparison with resveratrol (RSV) treatment. Forty-eight male Sprague-Dawley rats were randomly divided into the following four groups: standard chow diet (control group), high-fat diet (model group), HFD + abdominal massage (AM group), and HFD + resveratrol (RSV group). A rat model of IR was established by feeding HFD to rats for 8 weeks followed by treatment with AM or RSV for 4 weeks. The underlying HFD-induced IR molecular mechanisms were studied in rat serum and skeletal muscles. RSV and AM significantly improved glucose intolerance, hyperglycemia, obesity, and significantly reduced lipid accumulation [triglyceride (TC), total cholesterol (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)], adipocytokine [free fatty acids (FFA), adiponectin (ADPN)] and serum pro-inflammatory cytokines (IL-6 and TNF-α) secretion. In addition, AM activated the AMPK/SIRT1 signaling pathway in rat skeletal muscle. In conclusion, our results showed that AM could improve IR by regulating the secretion of adipocytokines, pro-inflammatory cytokines as well as related signaling pathways in the skeletal muscle of rats, which might provide insights into development of new treatment methods for the clinical treatment of IR.

Temporal trends and source apportionment of water pollution in Honghu Lake, China - Shuai Chen; Simeng Wang; Yanxi Yu; Mingjun Dong; Yanqiang Li (Environmental Science and Pollution Research, 2021)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Recent Progress in Dual-Polarization Radar Research and Applications in China - Kun Zhao; Hao Huang; Mingjun Wang; Wen-Chau Lee; Gang Chen; Long Wen; Jing Wen; Guifu Zhang; Ming Xue; Zhengwei Yang; Liping Liu; Chong Wu; et al. (Advances in Atmospheric Sciences, 2019)

Differential antigen expression between human eccrine sweat glands and hair follicles/pilosebaceous units - Leilei Cao; Liyun Chen; Haihong Li; Zairong Wei; Sitian Xie; Mingjun Zhang; Yao Lin; Haihua Huang (Journal of Molecular Histology, 2019)

Assessing pollution and risk of polycyclic aromatic hydrocarbons in sewage sludge from wastewater treatment plants in China’s top coal-producing region - Qihang Wu; Zhineng Liu; Junyan Liang; Dave T. F. Kuo; Shejun Chen; Xiaodong Hu; Mingjun Deng; Haozhi Zhang; YueHan Lu (Environmental Monitoring and Assessment, 2019)

Time course of differentiation of different cell types in 3D-reconstructed eccrine sweat glands - Mingjun Zhang; Haihong Li; Sitian Xie; Liyun Chen (Journal of Molecular Histology, 2018)

Over-Expressed FEZF1 Predicts a Poor Prognosis in Glioma and Promotes Glioma Cell Malignant Biological Properties by Regulating Akt-ERK Pathway - Mingjun Yu; Shijia Yu; Yixue Xue; Hai Yu; Duo Chen; Xiangtai Wei; Yunhui Liu (Journal of Molecular Neuroscience, 2018)

Three-dimensional reconstructed eccrine sweat glands with vascularization and cholinergic and adrenergic innervation - Mingjun Zhang; Haihong Li; Liyun Chen; Shuhua Fang; Sitian Xie; Changmin Lin (Journal of Molecular Histology, 2018)

Estimates of linkage disequilibrium and effective population sizes in Chinese Merino (Xinjiang type) sheep by genome-wide SNPs - Shudong Liu; Sangang He; Lei Chen; Wenrong Li; Jiang Di; Mingjun Liu (Genes & Genomics, 2017)

Expression of S100A2 and S100P in human eccrine sweat glands and their application in differentiating secretory coil-like from duct-like structures in the 3D reconstituted eccrine sweat spheroids - Haihong Li; Mingjun Zhang; Liyun Chen; Bingna Zhang; Cuiping Zhang (Journal of Molecular Histology, 2017)

Cell proliferation and differentiation during the three dimensional reconstitution of eccrine sweat glands - Xuexue Li; Haihong Li; Mingjun Zhang; Liyun Chen; Bingna Zhang (Journal of Molecular Histology, 2017)

Growth and photosynthetic responses of Ulva lactuca (Ulvales, Chlorophyta) germlings to different pH levels - Binbin Chen; Dinghui Zou; Mingjun Zhu (Marine Biology Research, 2017)

Foxa1 gene and protein in developing rat eccrine sweat glands - Haihong Li; Liyun Chen; Mingjun Zhang; Bingna Zhang (Journal of Molecular Histology, 2017)

Human eccrine sweat gland cells reconstitute polarized spheroids when subcutaneously implanted with Matrigel in nude mice - Haihong Li; Mingjun Zhang; Liyun Chen; Xuexue Li; Bingna Zhang (Journal of Molecular Histology, 2016)

Changes in keratins and alpha-smooth muscle actin during three-dimensional reconstitution of eccrine sweat glands - Haihong Li; Xuexue Li; Bingna Zhang; Mingjun Zhang; Wenlong Chen; Shijie Tang; Xiaobing Fu (Cell and Tissue Research, 2016)

Three-dimensional co-culture of BM-MSCs and eccrine sweat gland cells in Matrigel promotes transdifferentiation of BM-MSCs - Haihong Li; Xuexue Li; Mingjun Zhang; Lu Chen; Bingna Zhang; Shijie Tang; Xiaobing Fu (Journal of Molecular Histology, 2015)

Comparison of GCM-simulated isotopic compositions of precipitation in arid central Asia - Shengjie Wang; Mingjun Zhang; Fenli Chen; Yanjun Che; Mingxia Du; Yangmin Liu (Journal of Geographical Sciences, 2015)

Three-dimensional culture and identification of human eccrine sweat glands in matrigel basement membrane matrix - Haihong Li; Lu Chen; Mingjun Zhang; Shijie Tang; Xiaobing Fu (Cell and Tissue Research, 2013)

Molecular cloning of a novel subtilisin-like protease (Pr1A) gene from the biocontrol fungus Isaria farinosa - Zhangxun Wang; Huimin Meng; Zonglan Zhuang; Mingjun Chen; Ling Xie; Bo Huang (Applied Entomology and Zoology, 2013)

Design and Evaluation of a Novel Evodiamine-Phospholipid Complex for Improved Oral Bioavailability - Qunyou Tan; Shan Liu; Xueliang Chen; Mingjun Wu; Hong Wang; Huafeng Yin; Dan He; Huarong Xiong; Jingqing Zhang (AAPS PharmSciTech, 2012)

Cyclophilin A promotes human hepatocellular carcinoma cell metastasis via regulation of MMP3 and MMP9 - Mingjun Zhang; Chun Dai; Hengrui Zhu; Shuai Chen; Yanhua Wu; Qiang Li; Xianzhuo Zeng; Wenzhang Wang; Jie Zuo; Mei Zhou; Zongjun Xia; Guoqing Ji; et al. (Molecular and Cellular Biochemistry, 2011)

Characterization of a novel human HMBOX1 splicing variant lacking the homeodomain and with attenuated transcription repressor activity - Mingjun Zhang; Shuai Chen; Qiang Li; Yichen Ling; Jie Zhang; Long Yu (Molecular Biology Reports, 2010)